2005
DOI: 10.1016/j.asj.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multi-site investigation of patient satisfaction and psychosocial status following cosmetic surgery

Abstract: These results add to a growing body of literature documenting improvements in body image following cosmetic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 28 publications
1
47
0
4
Order By: Relevance
“…[21] Other psychological variables including depression and anxiety have also shown improvement following aesthetic surgery. [22] The findings of the current study are consistent with another study which reported high scores of depression among aesthetic rhinoplasty patients. [23,24] This study also supports the notion that an interest in aesthetic rhinoplasty is associated with a negative body image.…”
Section: Discussionsupporting
confidence: 82%
“…[21] Other psychological variables including depression and anxiety have also shown improvement following aesthetic surgery. [22] The findings of the current study are consistent with another study which reported high scores of depression among aesthetic rhinoplasty patients. [23,24] This study also supports the notion that an interest in aesthetic rhinoplasty is associated with a negative body image.…”
Section: Discussionsupporting
confidence: 82%
“…The response rate for mailed surveys is typically low, in the range of 49 to 66 percent, 5,[13][14][15][16] with various levels of completion. Existing generic breast questionnaires may lack sufficient specificity to assess the psychological impact of surgical changes.…”
Section: Methodsmentioning
confidence: 99%
“…In several interview studies using volunteer samples, North American women have disavowed external pressures or outside influences on their decisions to pursue surgery (Davis 1995;Gimlin 2000;Gagne and McGaughey 2002). However, in a multi-site study of female undergraduates at six U.S. universities, Sarwer et al (2005b) reported that 68% of respondents who had undergone surgery knew someone else who had, and another 30% identified a family member, a pattern repeated in samples of other American college students (Brown et al 2007;Delinsky 2005). A national survey of Norwegian women found a strong relationship between knowing someone who had surgery and high motivation to obtain surgery (von Soest et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…But a survey study of prospective cosmetic surgery patients in the U.S. found no significant difference in self-esteem between patients and a female control group , and self-esteem did not distinguish between women motivated and unmotivated to pursue surgery in Norway (von Soest et al 2006). The few studies with pre-and post-test designs reported contradictory findings: one showed 6 month postoperative increases in self-esteem measures for patients in Britain across seven different cosmetic surgery procedures (Klassen et al 1996) and two others using small and large multistate clinical samples of American women reported no statistically significant change postoperatively in selfesteem 2 months and 12 months respectively (Bolton et al 2003;Sarwer et al 2005b), a discrepancy potentially attributable to differences in length between surgery and follow up. Self-esteem likely does not operate singularly, however, since it has been found to vary with such things as age (Robins and Trzesniewski 2005;Schieman and Campbell 2001) and marital status groups (Cotten 1999;MacDonald et al 1987;Sinclair et al 2010).…”
Section: Introductionmentioning
confidence: 95%